Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18494/sam.2020.2697
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Thermoluminescent Slab Dosimeter for Postal Dosimetry Audit of External Radiotherapy Systems

Abstract: In this study, the feasibility of using a thermoluminescent slab dosimeter (TLSD) in postal dosimetry audit for radiotherapy systems is examined. First, changes in material structure are evaluated by measuring changes in TLSD weight and temperature after heating and cooling. Then, a fading correction factor is derived by measuring the relationship between the elapsed time after irradiation and thermoluminescence (TL) intensity. Finally, the uncertainty in the absorbed dosimetry using the TLSD with the TL absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The TL intensity was sharply faded 6 h after irradiation and gradual decay occurred after approximately 2 days after irradiation. Maruyama et al reported that TL intensity with their Cr‐doped Al 2 O 3 thermoluminescent slab dosimeter was sharply faded 24 h after irradiation and gradual decay occurred after 100 h 16 . Therefore, the TLDS we used in this study is considered to have slightly improved fading characteristics compared to their results.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The TL intensity was sharply faded 6 h after irradiation and gradual decay occurred after approximately 2 days after irradiation. Maruyama et al reported that TL intensity with their Cr‐doped Al 2 O 3 thermoluminescent slab dosimeter was sharply faded 24 h after irradiation and gradual decay occurred after 100 h 16 . Therefore, the TLDS we used in this study is considered to have slightly improved fading characteristics compared to their results.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, with the advent of the charge‐coupled device (CCD) camera, the high‐resolution imaging of large areas has become much faster, so the amount of research on photon imaging using 2D thermoluminescent dosimeter (TLD) has been increased 9–17 . Annalakshmi et al reported that manganese doped lithium triborate has a single grow peak and linear dose response to beta‐ray irradiation up to 50 Gy 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect ionizing radiation efficiently, the use of bulk materials is essential since the probability of an interaction between ionizing radiation and a detector material simply depends on the volume of the material. To satisfy this requirement, bulk single crystals, (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) ceramics, (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and glasses (32)(33)(34)(35)(36)(37)(38) have been applied for scintillators and dosimeters. Among these material forms, glasses have some advantages such as high chemical durability and high light transmittance, which are preferable for scintillator and dosimeter uses.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Since the TSL and OSL intensities are proportional to the incident radiation dose, storage phosphors are used for personal dose monitoring (8)(9)(10)(11)(12)(13) and imaging plates. (14)(15)(16)(17)(18)(19) So far, most research on scintillators and storage phosphors has been on various material forms including single crystals, (20)(21)(22)(23)(24) glasses, (25)(26)(27)(28)(29) and opaque ceramics. (30)(31)(32) In recent years, transparent ceramics have attracted much attention as a new material form.…”
Section: Introductionmentioning
confidence: 99%